THE EFFECT OF KAPPA CARRAGEENAN ADDITION ON THE EMULSION STABILITY OF MILKFISH (Chanos chanos) SAUSAGE - Edita Meliana; Tri Winarni Agustini; Retno Ayu Kurniasih (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2022)
Fish sausage is a processed fish product in the form of an emulsion, so that the stability of the emulsion is one of the most important factors for the success of the product. The aim of this study is to find out the effect of kappa carrageenan as a hydrocolloid in increasing the emulsion stability and determining the best concentration of kappa carrageenan based on the value of emulsion stability and the characteristics of milkfish sausage. The research method used was experimental laboratories with a completely randomized one-factor design using ANOVA, which was then continued with the HSD test. Organoleptic value data were analyzed using the Kruskal-Wallis and Mann-Whitney tests. The concentrations of kappa carrageenan used were 0%;0.5%;1%;1.5 with 3 repetitions. The results of the study show that kappa carrageenan addition has a significant effect (p<0.05) on the value of emulsion stability, sensory, moisture content, gel strength, and water holding capacity. The concentration of 1% kappa carrageenan (P2) was the best concentration with quality criteria: sensory of 8.14<µ<8.32, moisture content of 63.02%, water holding capacity of 55%, gel strength of 1200.14 g.cm, and emulsion stability of 83.23. Compared to other treatments, fish sausage with the addition of 1% kappa carrageenan has the brightest appearance according to the specific color of the product, has a chewy texture and solid but not hard, and has the highest value of emulsion stability.